OP0121 MANAGEMENT OF DYSLIPIDAEMIA AND HYPERTENSION IN PATIENTS WITH RHEUMATOID ARTHRITIS – DATA FROM 19 COUNTRIES. (2nd June 2020) - Rollefstad, S.; Ikdahl, E.; Sexton, J.; Kitas, G.; Van Riel, P.; Crowson, C. S.; Graham, I.; Semb, A. G.
Abstract : Background: The realisation that subjects with rheumatoid arthritis (RA) are at increased risk of cardiovascular disease (CVD) has led to a growing interest in risk factor control in such people, but whether this has influenced the management of dyslipidaemia and hypertension (HT) is uncertain. In subjects with coronary heart disease (CHD), audits of CVD risk factor control are regularly performed, which makes it possible to evaluate guideline implementation over time. 1 Updated surveys on CVD risk management in patients with RA are needed. Objectives: To describe differences in lipid and blood pressure (BP) levels among patients with RA from five world regions. Furthermore, to evaluate attainment of guideline recommended targets for lipid lowering and antihypertensive treatment. Methods: The SUrvey of CVD Risk Factors in patients with RA (SURF-RA) was conducted at 53 centres in 19 countries from 2014 to 2019. Data including demographics, RA disease characteristics, CVD comorbidity, risk factors and use of preventive treatment was collected. HT was defined as self-reported HT, and/or measured BP ≥140/90 mmHg, and/or use of anti HT medication (a-HT). The treatment goal of a-HT was BP <140/90 mmHg. The 10-year risk of a fatal CVD event was calculated by the European CVD risk calculator, the Systematic COronary Risk Evaluation (SCORE), and was thereafter multiplied with 1.5 as recommended by the European League Against Rheumatism. Patients were classified in a high or very high CVD risk group according to the 2012 European Society of Cardiology guidelines, with low density lipoprotein cholesterol (LDL-c) goal at <2.6 and <1.8 mmol/L, respectively. 2 Results: In total, 14503 RA patients were included. The mean age was 59.8±13.6 years, and it was a strong female preponderance (74%). Nearly 2/3 of the patients were hypertensive. Use of a-HT in the total population differed substantially between the cohorts with limited use in West Europe and Latin America (17.4% and 24.8%), in contrast to North America and East Europe (46.8% and 57.0%). On average, half of those with HT were at the recommended BP goal. The lowest BP goal attainment was seen in Asia, West and East Europe (40.8-43.1%), and the highest in North America (63.5%). Overall 51.5% had an indication for lipid lowering therapy (LLT), and of these 43.5% were taking LLT. Only 34.0% of patients with an indication for LLT were at recommended LDL-c goals. The proportion of RA patients on target for LDL-c varied greatly between regions, from 23.1% in East Europe to 51.0% in North America. The LDL-c goal attainment was higher in RA patients at high risk (45.1%) compared to those at very high risk of CVD (18.0%). Conclusion: This large international survey on RA patients revealed considerable geographical differences in CVD preventive treatment. Lower goal attainment for LLT than reported for subjects with CHD was observed. We conclude that there is a substantial need for improvement in CVD preventive measures in RA patients. References: [1]De Backer G, Jankowski P, Kotseva K, et al. Management of dyslipidaemia in patients with coronary heart disease: Results from the ESC-EORP EUROASPIRE V survey in 27 countries. Atherosclerosis . 2019;285:135-146. [2]Perk J, De Backer G, Gohlke H, et al. European Guide-lines on cardiovascular disease prevention in clinical practice. Eur Heart J. 2012:1635-701. Disclosure of Interests: Silvia Rollefstad: None declared, Eirik Ikdahl: None declared, Joe Sexton: None declared, Georeg Kitas: None declared, Piet van Riel: None declared, Cynthia S. Crowson Grant/research support from: Pfizer research grant, Ian Graham: None declared, Anne Grete Semb: None declared